Religion: naturalized, socialized, evaluated - Rolston, Holmes, 1932-2025, author; Cambridge University Press, publisher (Colorado State University. Libraries, 1999)
Evolutionary history on the prolific Earth, resulting in nature producing spirit (Geist). The origins of evil and sin in the genesis of human life. The necessity of suffering in evolutionary creation. Religion evolving to increase human fertility. Religion generating altruism, interpreted as both pseudoaltruism and as genuine altruism. The survival value of religion. Testing religions socially and cognitively. Creativity in actual and possible natural history as the genesis of information, the genesis of value, in which theists can detect transcendent divine presence.
Keywords: altruism; genesis; humans; religion; ethics; science; self-actualizing; fertility